Techniques in international law-making: extrapolation, analogy, form and the emergence of an international law of disaster relief - Sivakumaran, Sandesh (Oxford University Press, 2017)
This article traces the emergence of an international law of disaster relief from a patchwork of norms through to a holistic body of international law. It argues that, for many years, the international law of disaster relief existed in piecemeal fashion. As there is no overarching treaty on the subject at the global level, a hodgepodge of instruments have been concluded, namely subject-specific and disaster-specific treaties at the global level, regional and sub-regional agreements, bilateral agreements, as well as soft law. Since the 2000s, however, through the work of the International Law Commission and the International Federation of the Red Cross and Red Crescent, a holistic body of international law relating to disaster relief is in the process of emerging. The Article argues that this holistic body is in the process of emerging primarily as a result of three techniques which, while unconventional, are used relatively frequently in the making of international law. The three techniques are: (1) extrapolation from a series of piecemeal instruments to form a generalized standard; (2) the use of analogy; and (3) the conclusion of instruments that are soft in form but contain a mixture of hard law and soft law. The way in which the techniques have been used to develop a body of international law relating to disaster relief is analysed, their use in other fields of international law discussed, and limitations on their use in the disaster law context identified.